The Nutrient Density of Snacks - Julie Hess BA; Goutham Rao MD; Joanne Slavin PhD, RD (SAGE Publishing, 2017)
Background: Although Americans receive almost a quarter of their daily energy from snacks, snacking remains a poorly defined and understood eating occasion. However, there is little dietary guidance about choosing snacks. Families, clinicians, and researchers need a comprehensive approach to assessing their nutritional value. Objective: To quantify and compare the nutrient density of commonly consumed snacks by their overall nutrient profiles using the Nutrient-Rich Foods (NRF) Index 10.3. Methods: NRF Index scores were calculated for the top 3 selling products (based on 2014 market research data) in different snack categories. These NRF scores were averaged to provide an overall nutrient-density score for each category. Results: Based on NRF scores, yogurt (55.3), milk (52.5), and fruit (30.1) emerged as the most nutrient-dense snacks. Ice cream (−4.4), pies and cakes (−11.1), and carbonated soft drinks (−17.2) emerged as the most nutrient-poor snacks. Conclusions: The NRF Index is a useful tool for assessing the overall nutritional value of snacks based on nutrients to limit and nutrients to encourage.